EKSISTENSI PEMERINTAHAN PARTAI DALAM SISTEM KETATANEGARAAN INDONESIA - Suhaimi, Else (Nurani, 2019)
Within the framework of representative democracy, a general election is held every five years. These election include the election of legislative members, the election of president and vice president and the election of regional heads and regional deputy heads. The only participant in the election is a political party. Political parties have a strategic function which is to prepare candidates for the people’s representative, presidential candidates and vice presidential candidates as well as regional head and deputy regional head candidates. The vote acquisition of political in the Pileg, Pilpres and Pilkada determine the position of political parties in government. Party government begins nomination by political parties. Legislative members in addition to being representative of political parties who sit in factions according to the number of votes. Likewise after the presidential election, the presidential election and vice presidential pairs that are carried by a coalition of political parties indicate the existence of a seat of minister for the bearer political parties. Furthermore, after the elections, the pair of Pilkada, who were carried by a coalition of political parties indicated the existence of seat in regional government.